With(Out) a Little Help From My Friends? Reconciling Incongruous Findings on Stakeholder Management, Innovation, and Firm Performance. (January 2023) - Haefner, Naomi; Palmié, Maximilian; Leppänen, Petteri T.
Are stakeholder management and innovation substitutes or complements in affecting firm performance? Extant research provides support for both positions and thus leaves us with a puzzle. We conduct an exploratory fuzzy set qualitative comparative analysis (fsQCA) of 204 publicly listed European firms combining survey and archival data to formulate theory on how stakeholder management and innovation work (in)effectively together. Distinguishing between internal and external stakeholders and exploitative and exploratory innovation, we elaborate that managing for stakeholders and innovation can be both substitutes and complements depending on a set of contingencies. We discuss boundary conditions and implications for future research.